Fiscal Autonomy - Opportunity or Limitation for Innovative Local Development in Croatia? - Dubravka Jurlina Alibegovic (European Regional Science Association (ERSA), 2014)
This paper explores the role of Croatian large cities in financing local development projects. Croatian cities have limited autonomy in realization of public revenue. There are a small number of fiscal instruments to which cities can fully leverage or at least under the statutory limits can change the rates and thus affect the total amount of revenue collected. However, although they have limited ability to influence, cities insufficiently use fiscal instruments at their disposal for the planning and realization of budget revenue. Additionally there are several other factors that are recognized as major obstacles to local development financing. Most cities are unprepared to take on increased responsibilities for fund raising for economic development. In order to borrow responsibly, cities must have the ability to understand the impact of borrowing for infrastructure both annual debt service and annual operational and maintenance expenditures; and ability to identify, prioritize and plan capital investment. The additional problem for local development is structure of expenditures in local budgets. The majority of public expenditures in local budgets have been spent on providing a range of services aimed at ensuring access to education, health care and social protection to every citizen. Jointly these three public functions account for almost two-thirds of total sub-national government spending in Croatia. Contrary, public spending on investment amounts up to only 20% of sub-national budget expenditures. The key research questions of the paper are the following: (i) To what extent is the current structure of local budgets constraint to local development? (ii) What role has measurement of local fiscal capacity in providing transparent base for raising revenue at local level? (iii) How do large cities develop "joint visions" that integrate economic and social development? How can the governance system at local level promote better integration of these two objectives in transparent and effective way? (iv) What are the opportunities and limitations for financing development projects from various innovative financing sources such as: pooling private and public revenue, new revenue streams (e.g. voluntary contribution scheme) assigned to developmental activities on a multi-year basis, new incentives (financial guarantees, corporate social responsibility or other rewards) to remove market failures or to speed up ongoing developmental activities. The last section summarizes analysis and offers recommendations that can provide a platform for improvements in the field of financing of innovative local development in Croatia.
Keywords: H71; 330; local development; local public finance; fiscal autonomy; Croatia